76.8k views
3 votes
1. y = 6x
2x + 3y = -20

2 Answers

6 votes

Explanation:


y = 6x


2x + 3y = -20

To solve this system of equations, let's multiply the first equation by
-3 to get a
3y term in each equation:


-3y = -18x

Now, let's add the two equations together:


(2x + 3y) + (-3y) = -20 + (-18x)


2x = -20 - 18x


20x = -20


x = -1

Now, we can plug in this value of
x into either equation to solve for
y:


y = 6x


y = 6(-1)


y = -6

or


2x + 3y = -20


2(-1) + 3y = -20


-2 + 3y = -20


3y = -18


y = -6

Therefore, the solution to this system of equations is
(-1, -6).

User Mel Nicholson
by
6.1k points
2 votes

Answer:

x = -1

y = -6

Explanation:

y = 6x

2x + 3y = -20

Substitute the first expression into the second one

We have

2x + 3y = -20

2x + 3(6x) = -20

2x + 18x = -20

20x = -20

Divide both sides by 20 to isolate x

20x/20 = -20/20

x = -1

Remember the first expression

y = 6x

Therefore

y = 6(-1)

y = 6 x -1

y = -6

Check

2(-1) + 3(-6) = -20

-2 + -18 = -20

-2 - 18 = -20

-20 = -20

So our answer is correct

User Miles Henrichs
by
5.5k points